António e as Variações identitárias da cultura portuguesa contemporânea - Paula Guerra (Ciências Sociais Unisinos)
This article is focused on the preliminary analysis of a set of music lyrics by António Variações [Anthony Variations] (1983a, 1983b, 1984), which we consider representative of the multiple and plural identities that mark Portuguese cultural contemporaneity from the 1980s on. Approaching this musician has a double meaning: the way in which he represents the words of Fernando Pessoa when he pointed the importance of being “plural like the universe”; as well as the way in which each social actor can represent different social identities (to be at once Portuguese, a barber, catholic, from Braga, a musician and a variety artist). With this complex figure, it becomes important to analyze the cultural identity as a process (as a history and representation) that is plural, antynomous, recur- sive. This exercise is based on the need for a renovated epistemological understanding (Guerra, 2015b; Silva and Guerra, 2015; Guerra and Silva, 2014; Guerra and Januário, 2016) about the field of the arts as a producer of knowledge by representing the social reality in a proper and autonomous form, interfering in it and conditioning the analysis by generating interpretations of the instituted knowledge.